Effects of Pantoprazole in experimental acute pancreatitis - Hackert, Thilo; Tudor, Stefan; Felix, Klaus M.; Dovshanskiy, Dmitry; Hartwig, Werner; Simon, Wolfgang A.; Werner, Jens (Life sciences, 2010)
Aims - Oxidative stress with free radicals plays a crucial role in acute pancreatitis (AP). Pantoprazole (PPZ), widely used as a proton pump inhibitor, possesses reactivity towards hydroxyl radicals. The aim of the study was to examine the effect of PPZ on the course of experimental AP. - Main methods - Mild AP was induced in rats by caerulein (n=12). Severe AP was induced by infusion of glycodeoxycholic acid (10mM) into the pancreatic duct combined with caerulein (n=12). Both AP models were randomized to PPZ treatment (20mg/kg at baseline and after 12h) or placebo. Control animals received Ringer solution (n=6) without AP induction. After 24h severity of AP was examined by histology, enzyme levels, edema and inflammatory markers (myeloperoxidase, protein profiling). Furthermore, CD62P and CD31 for leukocyte and platelet activation were investigated. - Key findings - Histology showed that PPZ treatment reduced tissue infiltration of inflammatory cells and acinar cell necrosis in severe AP. After PPZ treatment CD62P expression in mild AP and CD31 expression in severe pancreatitis decreased, indicating an inhibition of platelet activation. In mild and severe AP, PPZ significantly decreased amylase, LDH, edema and myeloperoxidase activity. Protein profile of pancreatic juice and serum revealed different spectra and less pancreatic juice proteins in PPZ treated groups indicating less acinar cell leakage. - Significance - PPZ possesses anti-inflammatory in vivo properties and attenuates the course of AP. This is mediated via a reduced expression of inflammatory and adhesive proteins with a consecutive decrease in platelet and leukocyte activation as key steps in the pathogenesis of AP.
Gesehen am 12.06.2023